Cultural values of the Malay community through "Hikayat Misa Melayu" - Nik Mohamad Sharifuddin, Nik Nurul Azreen; Noor Muhammad, Salmah Jan (Human Resource Management Academic Research Society, 2019)
This research is about the cultural values that have been a traditional practice of the Malay community for decades. The culture covers a wide range of knowledge and not only the arts aspects. The culture inherited by the Malay community includes belief, traditions, customs, law and the lifestyle that have been practiced by the older generations. In this modernized era, the Malay community especially the younger factions have lesser understandings on the concept of culture and tend to look down upon the Malay culture itself the culture is the symbol of intellectuality of the Malay community because the culture would have not be created without experience and awareness from the society itself. Hence, this research focuses on the traditional culture of the Malay community embraced in the Hikayat Misa Melayu by Raja Chulan Raja Hamid in 1992. This research used Teori Pengkaedahan Melayu by Hashim Awang in 1989. The findings clearly portray the variety of traditional culture practiced by the previous generation including the royalties. Cultures highlighted by the writer have naturally been assimilated in the souls of the Malay community. Therefore, we hope this research is able to provide useful inputs to the society in hopes that the current generation will not alienate the Malay’s traditional culture in their daily lives.